A Systematic Review on Predisposition to Lymphoid (B and T cell) Neoplasias in Patients With Primary Immunodeficiencies and Immune Dysregulatory Disorders (Inborn Errors of Immunity) - Riaz, Irbaz Bin; Faridi, Warda; Patnaik, Mrinal M.; Abraham, Roshini S. (Frontiers in Immunology, 2019)
Primary immunodeficiencies and immune dysregulatory disorders (PIDDs; now referred to as inborn errors in immunity) are rare disorders (1) with a prevalence of 41.4 or 50.5 per 100,000 persons (2). The incidence of malignancy in PIDD patents is the second-highest cause of death in children as well as adults, after infection, and is higher in certain PIDDs compared to others. We performed a systematic review of the literature to identify reports of B cell and T cell neoplasias in PIDDs and clustered them based on their classification in the IUIS schema. As would be expected, higher susceptibility to malignancies are typically reported in patients with Common Variable Immunodeficiency (CVID), combined immunodeficiencies affecting cellular immunity, in particular, DNA repair defects, or in the context of impaired immune regulatory control. There is not much evidence of increased risk for cancer in patients with innate immune defects, indicating that not all types of infection or genetic susceptibility predispose equally to cancer risk. Viral infections, in particular EBV, HHV and HPV, have been shown to increase susceptibility to developing cancer, but also patients with defects in immune regulation, such as Autoimmune Lymphoproliferative Syndrome (ALPS), activated p110delta syndrome (APDS type 1) and IL-10 receptor deficiency among others have a higher incidence of neoplastic disease, particularly lymphomas. In fact, lymphomas account for two-thirds of all malignancies reported in PIDD patients(3), with either a combined immunodeficiency or DNA repair defect predominating as the underlying immune defect in one registry, or antibody deficiencies in another(4). The vast majority of lymphomas reported in the context of PIDDs are B cell lymphomas, though T cell lymphomas have been reported in a few studies, and tend to largely be associated with chromosomal breakage disorders (5) or Cartilage Hair Hypoplasia(6). There appears to be a much higher prevalence of T cell lymphomas in patients with secondary immunodeficiencies (7), though this could reflect treatment bias. We reviewed the literature and summarized the reports of B and T cell lymphoma in PIDD patients to survey the current state of knowledge in this area.